Mental Health and Happiness? Yes Please! - Vega Pérez, Héctor Ángel (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Mental health is the pinnacle of happiness and growth. We know that being a happy person is noteasy. The first step to being a happy person is to take care of your mental health. When you take careof your mental health, it is easier to recognize what can harm you physically and mentally. If you donot take care of your mental health, you will most likely end up falling into a deep pit of depression orsuffering from other detrimental problems, such as anxiety or stress. Another important reason whyyou should take care of your mental health is because, thanks to it, you can grow as a person. In otherwords, if you properly take care of your mental health, you can overcome many obstacles and moveforward in the future. For these reasons, mental health is the pinnacle of happiness and proper growth.Remember that mental health is not a joke.